HR Tech and staff training interaction - N. Yu. Kaufman; S. Yu. Zelentsova (Вестник университета, 2022)
The article explores the principles of building a competitive specialist in adigitally transformed economy, and presents the prerequisites that justify the development of staff training through the automation of HR technologies. The interpretation of the concepts «digital economy», «EdTech», «staff training», «gamification» is given. The main barriers preventing the implementation of HR Tech solutions in organisations are showed. The use of statistical analysis and comparison methods made it possible to present the areas of HR Tech, where digitalisation most actively improves and automates processes. It has been revealed that the main drivers of efficiency in the HR sphere can be modern tools and platforms that contribute to the introduction of automation in the personnel training system. The events of recent years have led to the understanding that it will no longer be possible to work effectively without the use of new technologies, therefore, the advantages of automating learning processes are highlighted. The role and area of responsibility of the training and development manager in the process of staff training has been established. Scenarios for solving the problem of a shortage of a digital specialist have been determined.